Financial Inclusion and Socio-Economic Development : The Mediating Role of Social Empowerment in Rural Odisha of India - Mohapatra, Amiya Kumar; Das, Ramesh Chandra; Khilar, Subhashree (Indian Journal of Finance, 2025)
Purpose : This study investigated the direct relationship between financial inclusion (FI) and socio-economic development (SED) of rural households in Odisha, India. Furthermore, the indirect relationship between financial inclusion and socio-economic development, with social empowerment (SE) as a mediating variable, was examined. Methodology : Data for the primary survey were collected from 545 rural households in Odisha, India, using a structured questionnaire. The study conducted exploratory factor analysis, confirmatory factor analysis, and path analysis to investigate the interrelationships among financial inclusion, socio-economic development, and social empowerment of households in rural Odisha. Findings : The primary research findings revealed that financial inclusion had a positive influence on the socio-economic development of rural households in Odisha, enhancing their access to formal banking and financial services. Another key finding was that social empowerment partially mediated the relationship between financial inclusion and socio-economic development. Furthermore, social empowerment contributed to the overall socio-economic well-being of these rural households and the rural economy by enlarging people’s choices and capabilities. Implications : This study underscored the importance of both direct and indirect pathways through which financial inclusion influences socio-economic development. The results would be helpful for the government, non-governmental organizations, and policymakers in guiding targeted interventions while preparing various financial inclusion and rural development programs. Financial institutions and financial service providers could use these insights to develop strategies that not only provide financial services to rural households but also design and support social empowerment initiatives. Originality : This research contributed to the existing literature by examining the impact of financial inclusion on rural households in Odisha and emphasizing the mediating role of social empowerment as a catalyst. It also studied multiple dimensions of financial inclusion and socio-economic development to improve the socio-economic conditions of these households in rural Odisha, India.